Answer Key 1.2

  1. \dfrac{42}{12}\div\dfrac{6}{6} = \dfrac{7}{2}
  2. \dfrac{25}{20}\div\dfrac{5}{5} = \dfrac{5}{4}
  3. \dfrac{35}{25}\div\dfrac{5}{5} = \dfrac{7}{5}
  4. \dfrac{24}{8}\div\dfrac{8}{8} = 3
  5. \dfrac{54}{36}\div\dfrac{9}{9} = \dfrac{6}{4}\div\dfrac{2}{2} = \dfrac{3}{2}
  6. \dfrac{30}{24}\div \dfrac{6}{6} = \dfrac{5}{4}
  7. \dfrac{45}{36}\div \dfrac{9}{9} = \dfrac{5}{4}
  8. \dfrac{36}{27}\div\dfrac{9}{9} = \dfrac{4}{3}
  9. \dfrac{27}{18}\div\dfrac{9}{9} = \dfrac{3}{2}
  10. \dfrac{48}{18}\div\dfrac{6}{6} = \dfrac{8}{3}
  11. \dfrac{40}{16}\div\dfrac{8}{8} = \dfrac{5}{2}
  12. \dfrac{48}{42}\div \dfrac{6}{6} = \dfrac{8}{7}
  13. \dfrac{63}{18}\div\dfrac{9}{9} = \dfrac{7}{2}
  14. \dfrac{16}{12}\div\dfrac{4}{4} = \dfrac{4}{3}
  15. \dfrac{80}{60} \div\dfrac{20}{20} = \dfrac{4}{3}
  16. \dfrac{72}{48}\div\dfrac{12}{12} = \dfrac{6}{4}\div\dfrac{2}{2} = \dfrac{3}{2}
  17. \dfrac{72}{60}\div\dfrac{12}{12} = \dfrac{6}{5}
  18. \dfrac{126}{108}\div\dfrac{9}{9} = \dfrac{14}{12}\div\dfrac{2}{2} = \dfrac{7}{6}
  19. \cancel{9} \cdot \dfrac{8}{\cancel{9}} =  8
  20. \cancel{-2}-1\cdot -\dfrac{5}{\cancel{6}3}=\dfrac{5}{3}
  21. 2 \cdot -\dfrac{2}{9} = -\dfrac{4}{9}
  22. -2\cdot \dfrac{1}{3}=-\dfrac{2}{3}
  23. \cancel{-2}-1\cdot \dfrac{13}{\cancel{8}4}=-\dfrac{13}{4}
  24. \dfrac{3}{2} \cdot \dfrac{1}{2} = \dfrac {3}{4}
  25. -\dfrac{\cancel{6}3}{5}\cdot -\dfrac{11}{\cancel{8}4}=\dfrac{33}{20}
  26. -\dfrac{3}{7} \cdot -\dfrac{11}{8} = \dfrac{33}{56}
  27. \cancel{8}4 \cdot \dfrac{1}{\cancel{2}1} = 4
  28. -2 \cdot -\dfrac{9}{7} = \dfrac{18}{7}
  29. \dfrac{\cancel{2}1}{\cancel{3}1} \cdot \dfrac{\cancel{3}1}{\cancel{4}2} = \dfrac {1}{2}
  30. -\dfrac{17}{\cancel{9}3} \cdot -\dfrac{\cancel{3}1}{5} = \dfrac{17}{15}
  31. \cancel{2}1 \cdot \dfrac{3}{\cancel{2}1} = 3
  32. \dfrac{17}{\cancel{9}3} \cdot -\dfrac{\cancel{3}1}{5} = -\dfrac{17}{15}
  33. \dfrac{1}{2} \cdot -\dfrac{7}{5} = -\dfrac{7}{10}
  34. \dfrac{1}{2} \cdot \dfrac{5}{7} = \dfrac{5}{14}
  35. \dfrac{\cancel{5}1}{2} \cdot -\dfrac{0}{\cancel{5}1} = -\dfrac{0}{2}\text{ or }0
  36. \underbrace{\dfrac{6}{0}}_{\text{undefined}} \cdot \hspace{0.25in}\dfrac{6}{7} = \text{no solution}
  37. -2 \cdot \dfrac{4}{7} = -\dfrac{8}{7}
  38. -\dfrac{\cancel{12}4}{7} \cdot -\dfrac{5}{\cancel{9}3} = \dfrac{20}{21}
  39. -\dfrac{1}{9} \cdot -\dfrac{2}{1} = \dfrac{2}{9}
  40. -2 \cdot -\dfrac{2}{3} = \dfrac{4}{3}
  41. -\dfrac{3}{2} \cdot \dfrac{7}{13} = -\dfrac{21}{26}
  42. \dfrac{5}{3} \cdot \dfrac{5}{7} = \dfrac{25}{21}
  43. -1 \cdot \dfrac{3}{2} = -\dfrac{3}{2}
  44. \dfrac{\cancel{10}5}{9} \cdot -\dfrac{1}{\cancel{6}3} = -\dfrac{5}{27}
  45. \dfrac{8}{9} \cdot \dfrac{5}{1} = \dfrac{40}{9}
  46. \dfrac{1}{\cancel{6}2} \cdot -\dfrac{\cancel{3}1}{5} = -\dfrac{1}{10}
  47. -\dfrac{9}{7} \cdot \dfrac{5}{1} = -\dfrac{45}{7}
  48. -\dfrac{13}{\cancel{8}1} \cdot -\dfrac{\cancel{8}1}{15} = \dfrac{13}{15}
  49. -\dfrac{2}{9} \cdot -\dfrac{2}{3} = \dfrac{4}{27}
  50. -\dfrac{4}{5} \cdot -\dfrac{8}{13} = \dfrac{32}{65}
  51. \dfrac{1}{\cancel{10}5} \cdot \dfrac{\cancel{2}1}{3} = \dfrac{1}{15}
  52. \dfrac{\cancel{5}1}{\cancel{3}1} \cdot \dfrac{\cancel{3}1}{\cancel{5}1} = 1
  53. \dfrac{1}{3}-\dfrac{4}{3} = -\dfrac{3}{3}\text{ or }-1
  54. \dfrac{1}{7}-\dfrac{11}{7} = -\dfrac{10}{7}
  55. \dfrac{3}{7} - \dfrac{1}{7} = \dfrac{2}{7}
  56. \dfrac{1}{3} + \dfrac{5}{3} = \dfrac{6}{3}\text{ or }2
  57. \dfrac{11}{6} + \dfrac{7}{6} = \dfrac{18}{6}\text{ or }3
  58. -2 - \dfrac{15}{8} \Rightarrow -\dfrac{16}{8} - \dfrac{15}{8} = -\dfrac{31}{8}
  59. \dfrac{3}{5}+ \dfrac{5}{4} \Rightarrow \dfrac{12}{20} + \dfrac{25}{20} = \dfrac {37}{20}
  60. -1- \dfrac{2}{3} \Rightarrow -\dfrac{3}{3} - \dfrac{2}{3} = -\dfrac{5}{3}
  61. \dfrac{2}{5}+ \dfrac{5}{4} \Rightarrow \dfrac{8}{20} + \dfrac{25}{20} = \dfrac {33}{20}
  62. \dfrac{12}{7} - \dfrac{9}{7} = \dfrac{3}{7}
  63. \dfrac{9}{8}- \dfrac{2}{7} \Rightarrow \dfrac {63}{56} - \dfrac{16}{56} = \dfrac {47}{56}
  64. -2+ \dfrac{5}{6} \Rightarrow -\dfrac{12}{6} + \dfrac{5}{6} = -\dfrac{7}{6}
  65. 1-\dfrac{1}{3} \Rightarrow \dfrac{3}{3} - \dfrac{1}{3} = \dfrac{2}{3}
  66. \dfrac{1}{2} - \dfrac{11}{6} \Rightarrow \dfrac{3}{6} - \dfrac {11}{6} = -\dfrac{8}{6} \text{ or } -\dfrac{4}{3}
  67. -\dfrac{1}{2} + \dfrac{3}{2} = \dfrac{2}{2}\text{ or }1
  68. \dfrac{11}{8} - \dfrac{1}{22} \Rightarrow \dfrac{121}{88} - \dfrac{4}{88} = \dfrac{117}{88}
  69. \dfrac{1}{5} + \dfrac{3}{4} \Rightarrow \dfrac{4}{20} + \dfrac {15}{20} = \dfrac {19}{20}
  70. \dfrac{6}{5} - \dfrac{8}{5} = -\dfrac{2}{5}

License

Icon for the Creative Commons Attribution-NonCommercial-ShareAlike 4.0 International License

Intermediate Algebra by Terrance Berg is licensed under a Creative Commons Attribution-NonCommercial-ShareAlike 4.0 International License, except where otherwise noted.

Share This Book